2017
DOI: 10.1002/elan.201700555
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Voltammetric Techniques for Ammonia Sensing in Ionic Liquids

Abstract: In electroanalytical chemistry, it is often observed that square wave voltammetry (SWV) and differential pulse voltammetry (DPV) are more sensitive techniques compared to linear sweep voltammetry (LSV), due to their method of sampling which minimises the charging current (non-faradaic processes). In this work, a comparison of the three techniques (LSV, DPV and SWV) is performed for ammonia (NH 3 ) gas oxidation (a chemically and electrochemically irreversible redox process) in an ionic liquid over a concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…DPV is a more sensitive approach compared to CV and hence, has been extensively used as a more sensitive method for the detection of molecules in low concentration [ 38 ]. In Figure 5 , the DPVs are recorded for the bare film electrode, as well as for each part that constitutes the final structure of OM-(KG) 5 -MOG 35-55 conjugate on the Graphite/SiO 2 working electrode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPV is a more sensitive approach compared to CV and hence, has been extensively used as a more sensitive method for the detection of molecules in low concentration [ 38 ]. In Figure 5 , the DPVs are recorded for the bare film electrode, as well as for each part that constitutes the final structure of OM-(KG) 5 -MOG 35-55 conjugate on the Graphite/SiO 2 working electrode.…”
Section: Resultsmentioning
confidence: 99%
“…As such, mannan was used as a carrier and conjugated to immunodominant MS peptides including MBP 83-99 , PLP 139-141 , and MOG 35-55 or their analogues, and were shown in animal models to tolerize T cells or switch Th1 cells to Th2 cells, depending on the peptide analogue used and showed stimulation of Th2 cells in peripheral blood mononuclear cells from patients with MS [ 17 , 21 , 33 , 34 , 35 ]. The conjugation of mannan, in its oxidized form (OM), to MOG 35-55 peptide (MOG 35-55 was used as an example in this study) via a (Lys-Gly) 5 linker [(KG) 5 ] was used and evaluated (OM-(KG) 5 -MOG 35-55 conjugate) using voltammetric techniques [ 1 , 2 , 3 , 4 , 36 , 37 , 38 ]. The conjugation between OM and peptide (MOG 35-55 ) occurs via formation of Schiff bases between the free amines of the linker (KG) 5 and aldehydes of OM.…”
Section: Introductionmentioning
confidence: 99%
“…Electrode materials made purely of metals give much more stable responses compared to screen-printed electrodes that are complicated by the presence of binders. Thin-film electrodes (TFEs), microarray thinfilm electrodes (MATFEs), and interdigitated electrodes (IDEs) have all been explored as new sensor surfaces in RTILs for the detection of ammonia [31,32] and oxygen [33] gases. The design of a commercially-available MATFE form MicruX is shown in Figure 3a; the WE consists of 90 recessed microdisk electrodes, in close proximity with the RE and CE.…”
Section: Planar or Printed Electrode Devicesmentioning
confidence: 99%
“…LODs of 6.2 ppm and 6.8 ppm, and sensitivities of 1.80 3 10 À9 A/ppm and 6.84 3 [41]. They pointed out that the LSV technique presents the best sensitivity among LSV, DPV (differential pulse voltammetry) and SWV (square wave voltammetry) for NH 3 sensing.…”
Section: Full Papermentioning
confidence: 99%
“…Compared with the results obtained by LSV, it is suggested that the LSV technique is more suitable and sensitive for lower concentrations of NH 3 with a higher sensitivity and a lower LODs. Similar behavior was reported by Hussain et al who studied voltammetric techniques comparison for NH 3 sensing in [C 2 mim][NTf 2 ] [41]. They pointed out that the LSV technique presents the best sensitivity among LSV, DPV (differential pulse voltammetry) and SWV (square wave voltammetry) for NH 3 sensing.…”
Section: Ammonia Sensingmentioning
confidence: 99%